Analisis Kinerja Sistem Komputasi Grid Menggunakan Perangkat Lunak Globus Toolkit Dan MPICH-G2 - Iqbal, Muhammad; Gani, R. A.; Ahdan, S.; Bakri, Muhammad; Wajiran, Wajiran (PTE FTK UIN Ar-Raniry, 2018)
The grid computation was developed by using fedora 14 operating system and globus toolkit software, NTP and certificate authority to built a grid system as well as MPICH-G2 as a reference to run parallel program. It was examined with matrix multiplication and was compared with single computation system based on processing time. This research employed 2 units of personal computer which earned a faster processing time than the single system, if only the program is divided into three process/jobs or more. If there was only 1 or 2 jobs, the process will not run faster than single computation. It can be concluded that the grid system will perform better if there are more nodes and core processor in each node and also balanced with the amount of the process/job.